Reconstruction of Online Gambling Law Enforcement: Symptoms of Decriminalization or Manifestations of Restorative Justice - Yuni Astriana; Mompang L Panggabean; Rospita Adelina Siregar (LUTUR Law Journal, 2026)
This study analyzes the legal implications due to the revocation of the norm of the criminal threat of online gambling in Article 45 paragraph (3) of the Electronic Information and Transaction Law through Law Number 1 of 2024. The legal gap between the ban that remains in effect and the sanctions that are removed raises law enforcement problems. The research method uses a normative juridical approach, this study examines the status of decriminalization and the prosecution transition strategy based on the principles of lex specialis derogat legi generali and lex favor rei. The results of the study show that the revocation cannot be interpreted as decriminalization, because the substance of the gambling ban is still regulated in the Criminal Code. The solution to handling cases, both existing and new, is to transfer the legal basis to Articles 426 and 427 of the Criminal Code. The technical strategy involves coordinating law enforcement and issuing the Minutes of Delik Adjustment to ensure legal certainty and justice during the transition period.